Heat shock protein-70 expression in vitiligo and its relation to the disease activity - Reham William Doss; Abdel-Azi; Amr M Abdel-Wahab; Yasser M Gohary; Laila A Rashed (Wolters Kluwer Medknow Publications, 2016)
Background: Vitiligo is a progressive depigmenting disorder characterized by the loss of functional melanocytes from the epidermis. The etiopathogenesis of vitiligo is still unclear. Heat shock proteins (HSPs) are prime candidates to connect stress to the skin. HSPs were found to be implicated in autoimmune diseases such as rheumatoid arthritis and other skin disorders as psoriasis. Aim and Objectives: The aim of this study was to map the level of HSP-70 in vitiligo lesions to declare its role in the pathogenesis and activity of vitiligo. Materials and Methods: The study included thirty patients with vitiligo and 30 age- and sex-matched healthy controls. Vitiligo patients were divided as regards to the disease activity into highly active, moderately active, and inactive vitiligo groups. Skin biopsies were taken from the lesional and nonlesional skin of patients and from the normal skin of the controls. HSP-70 messenger RNA (mRNA) expression was estimated using quantitative real-time polymerase chain reaction. Results: Our analysis revealed a significantly higher expression of HSP-70 mRNA in lesional skin biopsies from vitiligo patients compared to nonlesional skin biopsies from vitiligo patients (P < 0.001) and compared to skin biopsies from healthy controls (P < 0.001). The level of HSP-70 was not found to be correlated with age, sex, or disease duration. The expression of HSP-70 was correlated with the disease activity and patients with active vitiligo showed higher mean HSP-70 level compared to those with inactive disease. Conclusions: HSP-70 plays a role in the pathogenesis of vitiligo and may enhance the immune response in active disease.